Dysregulated bioenergetics: a key regulator of joint inflammation. Issue 12 (24th March 2016) - Biniecka, M; Canavan, M; McGarry, T; Gao, W; McCormick, J; Cregan, S; Gallagher, L; Smith, T; Phelan, J J; Ryan, J; O'Sullivan, J; Ng, C T; et al.
Abstract : Objectives: This study examines the relationship between synovial hypoxia and cellular bioenergetics with synovial inflammation. Methods: Primary rheumatoid arthritis synovial fibroblasts (RASF) were cultured with hypoxia, dimethyloxalylglycine (DMOG) or metabolic intermediates. Mitochondrial respiration, mitochondrial DNA mutations, cell invasion, cytokines, glucose and lactate were quantified using specific functional assays. RASF metabolism was assessed by the XF24-Flux Analyzer. Mitochondrial structural morphology was assessed by transmission electron microscopy (TEM). In vivo synovial tissue oxygen (tpO2 mmHg) was measured in patients with inflammatory arthritis (n=42) at arthroscopy, and markers of glycolysis/oxidative phosphorylation (glyceraldehyde 3-phosphate dehydrogenase (GAPDH), PKM2, GLUT1, ATP) were quantified by immunohistology. A subgroup of patients underwent contiguous MRI and positron emission tomography (PET)/CT imaging. RASF and human dermal microvascular endothelial cells (HMVEC) migration/angiogenesis, transcriptional activation (HIF1α, pSTAT3, Notch1-IC) and cytokines were examined in the presence of glycolytic inhibitor 3-(3-Pyridinyl)-1-(4-pyridinyl)-2-propen-1-one (3PO). Results: DMOG significantly increased mtDNA mutations, mitochondrial membrane potential, mitochondrial mass, reactive oxygen species and glycolytic RASF activity with concomitant attenuation of mitochondrial respiration and ATP activity (all p<0.01). This was coupled with altered mitochondrial morphology. Hypoxia-induced lactate levels (p<0.01), which in turn induced basic fibroblast growth factor (bFGF) secretion and RASF invasiveness (all p<0.05). In vivo glycolytic markers were inversely associated with synovial tpO2 levels <20 mm Hg, in contrast ATP was significantly reduced (all p<0.05). Decrease in GAPDH and GLUT1 was paralleled by an increase in in vivo tpO2 in tumour necrosis factor alpha inhibitor (TNFi) responders. Novel PET/MRI hybrid imaging demonstrated close association between metabolic activity and inflammation. 3PO significantly inhibited RASF invasion/migration, angiogenic tube formation, secretion of proinflammatory mediators (all p<0.05), and activation of HIF1α, pSTAT3 and Notch-1IC under normoxic and hypoxic conditions. Conclusions: Hypoxia alters cellular bioenergetics by inducing mitochondrial dysfunction and promoting a switch to glycolysis, supporting abnormal angiogenesis, cellular invasion and pannus formation.